Attitudes on children victims of sexual abuse and the relevance of poverty reduction policies in developing countries: A Tanzanian perspective - Bakta, Seraphina M. (World Conference on Child and Youth, 2024)
A research paper submitted to the Proceeding of the World Conference on Child and Youth, Vol. 1, 2019, pp. 1-11